Significance of preoperative C-reactive protein as a parameter in patients with small cell carcinoma of the esophagus - Feng, Ji-Feng (Dove Medical Press, 2013)
BACKGROUND: C-reactive protein (CRP) is inversely related to prognosis in many cancers, however, no studies regarding the predictive value of CRP in small cell carcinoma of the esophagus (SCCE) are available. The aim of this study was to determine the prognostic value of preoperative CRP in patients with SCCE. METHODS: From January 2001 to December 2010, a retrospective analysis of 43 consecutive patients with SCCE was conducted. Univariate and multivariate analyses were performed to evaluate the prognostic parameters. RESULTS: In our study, elevated CRP levels (>10 mg/L) were found in 16 patients (37.2%). CRP levels were significantly higher in patients with deeply invasive tumors (P = 0.018) and those associated with nodal metastasis (P = 0.018). Patients with CRP ≤10 mg/L had a significantly better overall survival than patients with CRP >10 mg/L (25.9% vs 6.3%, P = 0.004). Multivariate analyses showed that CRP was a significant predictor for overall survival. CRP >10 mg/L had a hazard ratio of 2.756 (95% confidence interval: 1.115–6.813, P = 0.028) for overall survival. CONCLUSION: Preoperative CRP is an independent predictive factor for long-term survival in patients with SCCE.